To conquer a highlander ebook - Wine, Mary (Hot Highlanders, 2010)
"Not to be missed." —Lora Leigh, New York Times #1 bestselling author of Black Jack A fierce Highland laird ready to kill for king and country... When Torin McLeren discovers his neighbor's plot against his king, he takes their daughter as his prisoner, thereby stopping her father's plot from going forward. But that leaves him with a woman under his roof whom he can't ignore, and not just because she's his enemy's daughter... A woman who's as much trouble as she is temptation... Shannon McBoyd decides to use her captor to experience passion for the first time, and then to destroy him. But her plan goes awry because once she has lured Torin into her bed, she no longer wants to hurt the one man who seems to value and understand her... Even if her father will kill him—and her—when he discovers what they've done... "Deeply romantic, scintillating, and absolutely delicious." —Sylvia Day, national bestselling author of The Stranger I Married "Mary Wine's writing is absolutely stellar." —CK2 Kwips & Critiques "Mary Wine has a definite knack for pacing, and the story never lets up." —Bookaholics